Restitution from public authorities in Ireland - Cleary, Niamh (Trinity College (Dublin, Ireland). School of Law, 2012)
This thesis examines the law of restitution from public authorities in Ireland. It operates on two levels. First, it is the first large scale research project on the law of restitution in Ireland. It also analyses the law of restitution in Ireland and considers how Ireland has integrated traditional principles of restitution that have been developed in other common law jurisdictions. Second, it examines the law of restitution as it applies to public authorities in Ireland. It considers the relationship between the law of restitution and principles of public law, and considers how principles of public law have shaped traditional restitutionary doctrines when these doctrines are invoked in claims for restitution from the state.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin